Cauldron - McDevitt, Jack (Ace Books, 2007)
When a young physicist comes up with an efficient star drive capable of reaching the core of the galaxy, retired star pilot Priscilla "Hutch" Hutchins embarks on a perilous mission into the far reaches of outer space to uncover the origins of the deadly Omega clouds.